Clifford, el pequeno perro colorado - Bridwell, Norman (New York : Scholastic, 1998)
Clifford begins life as a very small red puppy, but once he starts growing into a very large red dog there seems no limit to his potential size.
Keywords: Dogs -- Fiction; Size -- Fiction; Spanish language materials